Estudo de alternativas de fixação de implantes intramedulares poliméricos - Leopoldo Augusto Paolucci (2017)
The treatment and the reduction of bone fractures are usual procedures in human and veterinary orthopedic clinics. Fractures of long bones (e.g., femur, humerus, tibia) occur frequently both in humans and domestic large animals, requiring specific techniques of stabilization. Intramedullary nails, made from biocompatible materials, have been recognized as suitable for the treatment of long bone fractures. The development of prosthesis, presenting the necessary biocompatibility and mechanical strength to support bone stabilization demands, requires the understanding of the biomechanical behavior of the musculoskeletal system. To investigate the effect of different fixation strategies of the intramedullary interlocking nail (IIN) on the mechanical behavior of a polymeric implant applied for femoral fracture fixation in calves. It was also evaluated the performance of four polymeric materials used for the manufacture of intramedullary nails. Five Holstein male animals with a mean weight (± SD) of 62.8 ± 20.4 kgf and aged 74 ± 15 days were used in this study. Based on the solid model of the femur, sixteen models were built to simulate an oblique simple fracture. The models were divided into four groups, with each group of four models being associated with a different fixation strategy. Models were tested under the same loading condition that simulated a calf in the transition (decubitus position to static position) condition. Maximum bone and implant stresses were compared to yield and rupture stresses of specific materials (polyacetal, polypropylene, polyamide VI and a glass fiber-reinforced polymer). The largest stresses in the implant were found in the screws and at the interface between the screw and the nail. The performance of implants was influenced by the material and fixation strategy. The finite element method (FEM) model analyses demonstrated that all polymeric materials analyzed provided sufficient resistance to tolerate the loading forces imposed on the femur when an adequate fixation strategy was applied.